Gegevens over de vestiging aan de Kaap de Goede Hoop uit de Generale Missiven : Deel VI,1698-1713 (Historia, 2021)
-
Keywords: Willem Van Outhoorn; Joan van Hoorn; Governer general; Abraham van Riebeeck; Van Outhoorn; Generale Missiven